Vokal Bahasa Togutil Language - Mujahid Taha (Kantor Bahasa Provinsi Maluku Utara, 2016)
The study aims to figure out the forms of vowels in Togutil language (BT). The method is qualitative method. The object in this research is vocabulary that contains the vowel phonemes. The primary data of the research are taken through interview with native speakers of Togutil language in Dodaga Village, Tukur-tukur and Titipa village, districk of Wasile, east Halmahera. The result shows there are eight vocals: /a /, /æ/, /i/, /ɛ/, /e/, /u/, /o/, /ɔ/.